Persistence of Metarhizium brunneum (Ascomycota: Hypocreales) in the Soil Is Affected by Formulation Type as Shown by Strain-Specific DNA Markers - Iker Hernández; Clara Sant; Raquel Martínez; Marta Almazán; Marta Caminal; Víctor Quero; Mohammed El-Adak; Albert Casanova; Inmaculada Garrido-Jurado; Meelad Yousef-Yousef; Enrique Quesada-Moraga; José Manuel Lara; et al. (Journal of Fungi, 2023)
The genus Metarhizium has an increasingly important role in the development of Integrated Pest Control against Tephritid fruit flies in aerial sprays targeting adults and soil treatments targeting preimaginals. Indeed, the soil is considered the main habitat and reservoir of Metarhizium spp., which may be a plant-beneficial microorganism due to its lifestyle as an endophyte and/or rhizosphere-competent fungus. This key role of Metarhizium spp. for eco-sustainable agriculture highlights the priority of developing proper monitoring tools not only to follow the presence of the fungus in the soil and to correlate it with its performance against Tephritid preimaginals but also for risk assessment studies for patenting and registering biocontrol strains. The present study aimed at understanding the population dynamics of M. brunneum strain EAMb 09/01-Su, which is a candidate strain for olive fruit fly Bactrocera oleae (Rossi, 1790) preimaginal control in the soil, when applied to the soil at the field using different formulations and propagules. For this, strain-specific DNA markers were developed and used to track the levels of EAMb 09/01-Su in the soil of 4 field trials. The fungus persists over 250 days in the soil, and the levels of the fungus remained higher when applied as an oil-dispersion formulation than when applied as a wettable powder or encapsulated microsclerotia. Peak concentrations of EAMb 09/01-Su depend on the exogenous input and weakly on environmental conditions. These results will help us to optimize the application patterns and perform accurate risk assessments during further development of this and other entomopathogenic fungus-based bioinsecticides.